NCTM’s Principles and Standards for Developing Conceptual Understanding in Mathematics - Saleh Haji; Yumiati (Talenta Publisher, 2019)
The purpose of this study is to develop understanding of concepts in mathematics through the application of the NCTM's Principles and Standards. This research method is descriptive. The results obtained are understanding concepts in mathematics can be developed through the application of NCTM Principles and Standards consisting of 6 principles, namely: 1. Equity, 2. Curriculum, 3. Teaching, 4. Learning, 5. Assessment, and Technology. Understanding concepts in mathematics that can be developed are: a. defining concepts verbally and in writing, b. Make examples and not examples, c. Using various symbols to present a concept, d. Change the form of representation to various forms, e. Identifying the characteristics of a concept, f. compare various concepts, and g. interpret concepts.